2022
DOI: 10.1111/basr.12295
|View full text |Cite
|
Sign up to set email alerts
|

Market reaction to fossil fuel divestment announcements: Evidence from the United States

Abstract: Fossil fuel divestment movements have gained momentum since 2011, aimed at ending fossil fuel use and a move toward a cleaner, affordable, and sustainable energy system, for business and society. The present study investigates the direct impact of fossil fuel divestment announcements on stock prices of firms listed on the United States' stock exchanges. Using an event study and guided by the United Nation's sustainable development goals (SDGs), we test the effects of 116 divestments announcements between 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…There is ample evidence that divesting from fossil fuels does not increase the financial risk of the organizations that do so (Trinks et al 2018;Bassen et al 2021;Plantinga and Scholtens 2021). However, there is mixed evidence on whether divestments inflict significant economic harm on fossil fuel companies (Dordi and Weber 2019;Hansen and Pollin 2022;Zori et al 2022). This disagreement could suggest that not enough organizations have divested from fossil fuels to have a significant impact, meaning that designing behavioral interventions based on research about organizational leaders' divestment decisions could be particularly helpful.…”
Section: Illustrative Example: the Fossil Fuel Divestment Movementmentioning
confidence: 99%
“…There is ample evidence that divesting from fossil fuels does not increase the financial risk of the organizations that do so (Trinks et al 2018;Bassen et al 2021;Plantinga and Scholtens 2021). However, there is mixed evidence on whether divestments inflict significant economic harm on fossil fuel companies (Dordi and Weber 2019;Hansen and Pollin 2022;Zori et al 2022). This disagreement could suggest that not enough organizations have divested from fossil fuels to have a significant impact, meaning that designing behavioral interventions based on research about organizational leaders' divestment decisions could be particularly helpful.…”
Section: Illustrative Example: the Fossil Fuel Divestment Movementmentioning
confidence: 99%
“…In recent years, the interest in alternative and renewable energy sources has surged due to the escalating global population, the increasing energy demand, the dwindling reserves of fossil fuels, and the adverse effects of these fuels on human health and the environment, primarily through the rise in carbon dioxide levels in the atmosphere from combustion (Vaka et al, 2020;Zori et al, 2022). When examining Turkey's energy situation, it is observed that the country relies on external sources for approximately 70% of its total energy and is highly dependent on oil, accounting for about 90%.…”
Section: Introductionmentioning
confidence: 99%